Analysis of the interactive meaning of journalistic images of the human papillomavirus vaccine and the perceptions of female undergraduate students - Jingxi Chen; Ran Tao; Qiaomin Guo (Elsevier, 2020)
Objectives: This paper focuses on the underlying mechanisms of women's perceptions of persuasive visual health information. Methods: In the image viewing process, a separation between the image producer and the image viewer occurs, and the connection between the two is fractured. This mixed method research included modal discourse analysis (coding based on visual grammar theory), an eye tracking experiment, a questionnaire survey, and in-depth semi-structured interviews. The interactive meanings of journalistic images related to the human papillomavirus (HPV) vaccine were identified through four sets of codes. In addition, the perceptions of female viewers were analyzed. Results: In the first set of stimuli, i.e., the infographic, the female participants focused most of their attention on information about the nine-valent HPV vaccine. An analysis of the interactive meaning of two sets of journalistic pictures, i.e., fictional pictures and nonfictional pictures, indicated that the image producers did not implement useful viewer involvement strategies to persuade viewers. Furthermore, female viewers focused their attention on the "similar other" during the viewing process, gazing at the patient the longest as the primary area of interest (AOI). Conclusions: The study indicates that the current persuasive visual information about the HPV vaccine needs further improvement due to the high demand for information about HPV from the Chinese female audience.